Introduction - Havik, Klaske; Oliveira, Susana (Writingplace, 2023)
The special issue Writing Urban Places: New Narratives for the European City, marks the culmination of an international research network that delved into the intricate interplay between communities, urban spaces and narratives. At its core, this endeavour introduced an inventive approach aimed at deepening our comprehension of urban communities, their dynamics and their rootedness, all through the lens of narrative methodologies. This collection gives an account of the dynamics of this network of academics, which consists of over 175 individuals from 35 different European countries and a variety of disciplinary backgrounds. As such, the issue offers a conclusion to the Writing Urban Places COST Action while also providing a springboard for further reflections and discussions on urban narratives, and the role these could play in spatial developments in the European city.